Pencegahan Penggunaan Narkoba pada Remaja dengan Gerakan Sosialisasi Anti Narkoba di MTsS TPI Desa Tanjung Putus - Lubis, Ramadan; Safran, Safran; Zunidar, Zunidar; Fiqri, Muhammad (MASALIQ, 2023)
Drug abuse is currently very worrying, especially among teenagers. Based on data obtained from the National Narcotics Agency entitled Indonesia Drug Reports 2023, in 2022 the number of cases of drug users will be around 4.8 million, and East Java will be the province with the most cases in 2022, followed by North Sumatra in second place. The writer from the PEMA Team of PGMI Study Program, Faculty of Tarbiyah and Teaching Sciences, State Islamic University of North Sumatra carried out an anti-drug outreach activity which was held at MTsS TPI Tanjung Putus on July 20 2023 in an effort to prevent drug use in adolescents in Tanjung Putus Village. The purpose of this activity is for teenagers to understand about drug abuse and the impact of drug use. The expected target in this activity is that teenagers avoid drug use through the implementation of outreach activities by the PEMA Team.